Tree Improvement Work on Eucalyptus Tereticornis in India - An overview - Sharma, S. K. (Indian Forester, 2014)
In this overviewvarious aspects of genetic tree improvement of Eucalyptus tereticornis have been covered,which include provenance variation, seed stand, seed production areas, seedling seed orchard, and clonal seed orchard, hybridization andvegetativepropagation.Workrelatedtoapplicationof tissueculturetechnique has also been incorporated.